Integration of miRNA‐regulatory networks in hepatic stellate cells identifies TIMP3 as a key factor in chronic liver disease. (5th May 2020) - Azar, Fida; Courtet, Kevin; Dekky, Bassil; Bonnier, Dominique; Dameron, Olivier; Colige, Alain; Legagneux, Vincent; Théret, Nathalie
Abstract: Background & Aims: Activation of hepatic stellate cells (HSC) is a critical process involved in liver fibrosis. Several miRNAs are implicated in gene regulation during this process but their exact and respective contribution is still incompletely understood. Here we propose an integrative approach of miRNA‐regulatory networks to predict new targets. Methods: miRNA regulatory networks in activated HSCs were built using lists of validated miRNAs and the CyTargetLinker tool. The resulting graphs were filtered according to public transcriptomic data and the reduced graphs were analysed through GO annotation. A miRNA network regulating the expression of TIMP3 was further studied in human liver samples, isolated hepatic cells and mouse model of liver fibrosis. Results: Within the up‐regulated miRNAs, we identified a subnetwork of five miRNAs (miR‐21‐5p, miR‐222‐3p, miR‐221‐3p miR‐181b‐5p and miR‐17‐5p) that target TIMP3. We demonstrated that TIMP3 expression is inversely associated with inflammatory activity and IL1‐ß expression in vivo. We further showed that IL1‐ß inhibits TIMP3 expression in HSC‐derived LX‐2 cells. Using data from The Cancer Genome Atlas (TCGA), we showed that, in hepatocellular carcinoma (HCC), TIMP3 expression is associated with survival ( P  < .001), while miR‐221 ( P  < .05), miR‐222 ( P  < .01) and miR‐181b ( P  < .01) are markers for a poor prognosis. Conclusions: Several miRNAs targeting TIMP3 are up‐regulated in activated HSCs and down‐regulation of TIMP3 expression is associated with inflammatory activity in liver fibrosis and poor prognosis in HCC. The regulatory network including specific miRNAs and TIMP3 is therefore central for the evolution of chronic liver disease.